Can red blood cell distribution width (RDW) predict clinical and endoscopic activity in ulcerative colitis patients? - Pülat, Hüseyin; Yalaki, Serkan (Journal of Surgery and Medicine, 2020)
Aim: Classification of ulcerative colitis (UC) according to disease activity and severity is important in clinical practice for it determines the management of the patient. In this study, we aimed to investigate the relationship between red blood cell distribution width (RDW) and clinical activity index (CAI) in UC patients as well as endoscopic activity indexes (EIA) that determine disease severity relative to mucosal disease. Methods: This research was planned as a case-control study. Ninety-nine patients diagnosed with UC were divided an active disease group and a remission group according to their clinical and endoscopic findings. Age and gender-matched control groups were formed from 56 individuals with normal colonoscopic findings. Results: Serum RDW levels were significantly higher in the UC group (P<0.001). In post-hoc comparisons, a statistically significant difference was observed between the control group and active disease groups (P<0.001). However, RDW values did not significantly predict clinical and endoscopic activity in either the active disease or the remission groups (P=0.05 and P=0.09, respectively). In predicting clinical and endoscopic activity indices, the cut-off values of RDW were 14.25 (66% sensitivity and 72% specificity) and 13.75 (64% sensitivity and 62% specificity), respectively. Conclusion: This study showed that RDW can be used as a marker for disease activity in ulcerative colitis, but it did not show the same efficacy in remission and active disease distinction.